Total Moral Quality sebagai Konsep Pendidikan Karakter di Pesantren; Sebuah Kajian Kritis Pemikiran Hasan Baharun - Chusnul Muali; Robiatul Aini (Cendekia: Kependidikan dan Kemasyarakatan, 2019)
Abstract: This paper will present the concept of character education in Islamic boarding schools that have provided many benefits to the community. Islamic boarding schools are the right place to implement character education. In Hasan Baharun's concept, the concept of character education in Islamic boarding schools is called Total Moral Quality (TMQ). In this case the researcher is interested in examining whether this concept is very influential on the character of students by doing research in Islamic boarding schools. That way the researcher can conclude that, Total Moral Quality (TMQ) said by Hasan Baharun is the concept of education that is very influential on the character of students in the pesantren. because, in this concept will form a perfect human being who always makes noble character as a basis in every activity of his life.الملخص : ستعرض هذه الورقة مفهوم تعليم الشخصيات في المدارس الداخلية الإسلامية التي قدمت العديد من الفوائد للمجتمع. المدارس الداخلية الإسلامية هي المكان المناسب لتنفيذ تعليم الشخصيات. في مفهوم حسن بهارون ، يسمى مفهوم تعليم الشخصيات في المدارس الداخلية الإسلامية "الجودة الأخلاقية الشاملة" (TMQ) ، وفي هذه الحالة يهتم الباحث بفحص ما إذا كان هذا المفهوم له تأثير كبير على طبيعة الطلاب من خلال إجراء الأبحاث في المدارس الداخلية الإسلامية. وبهذه الطريقة ، يمكن للباحث أن يخلص إلى أن الجودة الأخلاقية الشاملة (TMQ) التي قالها حسن بهارون هي مفهوم التعليم المؤثر جداً على شخصية الطلاب في المدارس الداخلية. لأنه ، في هذا المفهوم سوف يشكل الإنسان المثالي الذي يجعل دائما شخصية النبيل كأساس في كل نشاط من حياته